2001
DOI: 10.1097/00041327-200106000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Pituitary Hypophysitis

Abstract: The case of a young woman who developed lymphocytic hypophysitis 2 weeks after delivery of a healthy baby is reported. The patient presented with clinical features suggestive of a pituitary mass lesion, but surgery was avoided when other clinical and radiologic features were considered. The patient recovered with steroid treatment only. We review the literature on this increasingly recognized condition and argue that medical management may be more suitable than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, endocrinological and neuroradiological improvement under pre-or postoperative high-dose corticosteroids is most often not only incomplete, but also only transient or even fails (8,10,14,20,(23)(24)(25)(26)(27)(28)(29). The only prospective trial of glucocorticoid use in lymphocytic hypophysitis showed that methylprednisolone reduced MRI mass in seven out of nine patients and improved anterior pituitary function in four patients (8,15,16,21).…”
Section: Lymphocytic (Nz21)mentioning
confidence: 99%
“…However, endocrinological and neuroradiological improvement under pre-or postoperative high-dose corticosteroids is most often not only incomplete, but also only transient or even fails (8,10,14,20,(23)(24)(25)(26)(27)(28)(29). The only prospective trial of glucocorticoid use in lymphocytic hypophysitis showed that methylprednisolone reduced MRI mass in seven out of nine patients and improved anterior pituitary function in four patients (8,15,16,21).…”
Section: Lymphocytic (Nz21)mentioning
confidence: 99%
“…Additionally, corticotroph axis recovery and the need for rescue therapy were significantly better with very high dose glucocorticoids. Early involvement of ACTHsecreting cells in PAH and subsequent hypocortisolism has been proposed to be an underlying mechanism of perpetuating the autoimmune destruction of multiple tropic hormones (20). Hence, corticotroph axis recovery by higher doses (>100 mg/day) of glucocorticoids given intravenously may have a role in preventing damage to adjacent pituitary cell types and lead to better APH recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytic hypophysitis is a rare but increasingly recognised pituitary disorder which affects women at the end of pregnancy or in the immediate post-partum period [1] most commonly, although it may occur independently of pregnancy in persons of either sex [2]. The aetiology is unknown but there is a relationship with other autoimmune diseases, particularly There are no features of adenoma, nor were granulomata seen.…”
mentioning
confidence: 99%
“…The differential diagnosis of this lesion includes an expanding pituitary adenoma or meningioma, both of which may enlarge considerably during pregnancy [8], infective processes such as tuberculosis, pyogenic or fungal sinus disease or mucocoele, and granulomatous disease, particularly sarcoidosis which may commonly affect the hypothalamus and pituitary [9]. No other case has been reported so early in pregnancy and hence a clear treatment protocol during pregnancy is required; in post-partum cases a trial of steroids seems justified, with recourse to surgery only if the lesion fails to resolve or grows larger, as advocated by Tubridy et al [1]; similarly in very late pregnancy the same treatment plan can be used, or a delay in surgery until after a planned caesarian section. What, therefore should be done in the middle trimester?…”
mentioning
confidence: 99%